First record of the dusky grouper Epinephelus marginatus (Actinopterygii: Epinephelidae) undergoing sexual transition in the South Western Atlantic, Brazil - Condini, Mario V. (2013)
The dusky grouper Epinephelus marginatus historically exploited by fisheries is a marine species showing slow growth, late maturation and protogynous hermaphroditism. Currently, it is considered as endangered by the IUCN. Therefore, it is essential to increase the knowledge about its biology and ecology to help conservation of this species. The present study reports the first record of a dusky grouper individual undergoing sexual transition, from female to male, in the Atlantic Ocean based on histological analyses of gonads. The specimen with total length: 770 mm; total weight: 8.1 kg and age: 21 years was captured in a rocky bottom along the coastline of the southernmost in Brazil.